Effect of flushing and oestrus synchronization application on fertility in Akkaraman sheep - Esen, F; Bozkurt, T (Scientific Technical Research Council Turkey, 2001)
In this study, the effect of flushing and oestrus synchronization applications on fertility in Akkaraman sheep was investigated. The research was carried out in 78 Akkaraman sheep at the second lactation. The sheep were randomly allocated into two groups; one being the experimental group and the other the control group. Vaginal sponge containing fluorogestone acetate (FGA) and oestrus synchronization using 600 I.U. PMSG was applied to the experimental group. Flushing was also applied only to the sheep in the experimental group. Pregnancy rates of 90% and 92% were obtained in the experimental and control groups, respectively. 87% of the pregnant sheep gave birth in both groups. Twin birth, average lamb number to each birth and lamb number at weaning were found to be 57% and 6% (P<0.01). 1.77 and 1.06 (P<0.01), 105% and 79% (P<0.05) in the experimental and control groups, respectively.
Akkaraman Irki Koyunlarda Flushing ve Östrus Senkronizasyonu Uygulamasinin Dölverimi Üzerine Etkisi
Keywords: sheep; flushing; synchronization; fertility